Mentalisation, Self-Compassion, and the Psychosocial Impact of ADHD in Adult Women - Kate Witteveen; Denis O'Hara (Psychotherapy and Counselling Journal of Australia, 2025)
This study developed a brief measure of the psychosocial impact of attention-deficit/hyperactivity disorder (ADHD) and explored relationships between mentalisation, self-compassion, and the psychosocial impact of ADHD in adult women. The study hypothesised that lower mentalisation would correspond to higher psychosocial impact and that self-compassion would act as a mediator of this relationship. In Phase 1, a new measure, the ADHD Impact on Psychosocial Functioning (AIPF), was administered to a sample of women with a diagnosis of ADHD (N = 388), and a preliminary investigation of its psychometric properties was undertaken. Psychometric analyses provided preliminary support for the internal consistency and construct validity of a two-factor structure of the AIPF, and it was therefore retained for Phase 2. In Phase 2, the Mentalisation Scale, the Self-Compassion Scale—Short Form, and the AIPF were administered to an additional sample of women with ADHD (N = 89). Analyses revealed that self-mentalisation was significantly lower than other dimensions of mentalisation. As hypothesised, low self-mentalisation was associated with high psychosocial impact of ADHD, and this was fully mediated by self-compassion. These findings highlight the unique role of self-mentalisation as a predictor of negative psychosocial outcomes in women with ADHD and provide additional evidence of the protective role of self-compassion. Together, these findings suggest the potential benefits of therapeutic interventions focusing on the augmentation of self-mentalisation and self-compassion in women with ADHD. Limitations of the current study and recommendations for future research are discussed.